Methicillin-resistant staphylococcus aureus (MRSA) SPA type T032 overtakes MRSA SPA type T037 as the predominant clonal strain: preliminary findings from a Malaysian tertiary hospital - Faisal, Ummu Salamah; Abdul Samat, Muttaqillah Najihan; Neoh, Hui-min; Ahmad Zaidi, Nur Adnin; Zainulabid, Ummu Afeera; Salleh, Sharifah Azura (2022)
Community and hospital-acquired strains of Methicillin-resistant Staphylococcus aureus (MRSA) continue to pose a threat worldwide. Molecular epidemiological studies conducted worldwide continue to demonstrate shifts in predominantly circulating MRSA clones peculiar to their centres or countries that have the propensity to cause infection in hospitals and the community. We aimed to detect our hospital's predominantly circulating MRSA clonal strain in 2016 and 2018 by spa typing to compare with predominant clones reported previously in our and other Malaysian hospitals.